Dynamic Characteristics of Accelerator-Driven Subcritical Reactor With Self-Adapting Multi-Mode Core Few-Group Constants - Deng, Nianbiao; Xie, Jinsen; Hou, Cheng; Zeng, Wenjie; Chen, Zhenping; Yu, Tao; Zhao, Pengcheng; Liu, Zijing; Xie, Chao; Xie, Qin (Frontiers in Energy Research, 2021)
In this study, the dynamic characteristics of accelerator-driven subcritical reactor (ADSR) under beam transients with high heterogeneity of neutron flux in time-space are investigated. Multi-mode core few-group constants are generated by three kinds of neutron fluxes: steady state of ADSR, λ-eigenvalue fundamental wave, and α-eigenvalue fundamental wave. The proposed few-group constants overcome the limitation of single few-group constant generated by two-step method that cannot consider the variation in neutron flux density and neutron energy spectrum with time and space. Compared to the existing few-group constants generated by two-step method under different operating conditions, the self-adapting multi-mode core few-group constants exhibit higher accuracy in the case of following two modes: steady-state mode of ADSR in the starting process and λ-eigenvalue mode in the beam trip condition. Overall, this research provides useful insights on neutron kinetics and can boost the development of ADSRs.